The Three Cultural Lines of Buddhist, Christian and Islamic Communities in Phrapradaeng District, Samutprakarn Province: A Model of Peaceful Coexistence toward ASEAN Community - Peammatha, Jakpong; Toprayoon, Yannakorn; Nunchan, Akrakit; Chachaeng, Kittipat (Journal of International Buddhist Studies, 2018)
The Phrapradaeng District is the smallest district of Samutprakarn province. For over the past centuries, it is composed of the different ethnic and religious groups of people. In this paper, the common identities of the three cultural lines of Buddhist, Christianity and Islamic communities were investigated and to strengthen the affection, unity, and preparedness entering the ASEAN Community. The qualitative research method was adopted, using field observation and focus group; observation and group interviews. The results demonstrated that the identities of all three religions and communities were different; the community-based religious principles have stipulated and promoted the behaviors of the people; namely, living in the way of righteousness, and social norms and cultures that are recognizable and known, loving fellowman, appreciation, forgiveness as religious teaching in the three communities. It’s suggested that the three cultural line networks of philosophers should be established and annual activities should be promoted actively.